Telework: an analysis of provisional measure 1046/2021 as a measure to face the public health emergency arising from COVID-19 (Research, Society and Development, 2021)
Telework is a new modality in employment relationships. For this reason, there are some difficulties regarding its application. The research problem is to conceptualize telework and its relationship with the COVID-19 pandemic. The objective is to analyze the historical concept of its creation and analyze the parameters of its application in contemporary society, listing the form of origin, as well as the facility with the employer and employment. The methodology used for the elaboration of the work was descriptive and bibliographic exploratory research, which will consist of an analysis of scientific articles, books, articles in electronic journals, analysis of laws, thus being a documentary research in the labor sphere, resulting from the COVID-19 that had its peak in the beginning of the year 2020 in Brazil. The research result allows us to understand the new employment methods and their application to the labor market, as well as the physical and mental aspects resulting from their use, in a way that brings benefits to the worker and employer, as a closer look is needed. that the use of telematic means does not overload the worker.